Paenibacillus sp., as a promising candidate for development of a novel technology of inoculant production - Kozyrovska, N.O.; Negrutska, V.V.; Kovalchuk, M.V.; Voznyuk, T.N. (Біополімери і клітина, 2005)
A bacterial strain IMBG156 producing exopolysaccharide (EPS) was isolated from siliceous rock and identified as a Paenibacillus species by partial sequencing its 16S rDNA. Paenibacillus sp. IMBG156 was used in a novel technology for inoculant production based on co-cultivating this bacterium with any bacterium of choice. Paenibacillus sp. provides in situ the bacterial cells of the inoculant with EPS, a carrier, and most likely with a source of carbon and energy. The partner bacterium designates a type of inoculant (biopesticide or biofertiliser). The strain IMBG156 does not destroy the signaling system of Gram-negative partners, based on acylated homoserine lactones, stimulates plant growth, and is rather competitive in the plant rhizosphere and soil. A prototype of the inoculant based on dual-culture Paenibacillus sp. IMBG156 - Pseudomonas sp. IMBG163 exhibits a noticeably longer shelf life than monoculture of Pseudomonas sp. IMBG163. (ЕПС), виділено з силікатної породи та ідентифіковано як Paenibacillus sp. на основі визначення первинної нуклеотидної послідовності 16S рДНК Paenibacillus sp. IMBG156 використа но у технологи виробництва мікробних препаратів, яка базуться на спільному культивуванні цієї бактерії та бактерії за вибором. Paenibacillus sp. постачає in situ бактерійні клітини носієм (ЕПС) та, найвірогідніше, є джерелом вуглецю і енергії. Бактерія-партнер визначає тип препарату (біодобриво, біопестицид). Штам IMBG156 не пошкоджує сигнальної системи грамнегативних бактерій-партнерів, яка грунтується на ацильованих гомосеринлактонах, стимулює ріст рослини і є доволі конкурентною у ризосфері. У демонстраційному препараті, створеному на основі бактерій-партнерів Paenibacillus sp. IMBGI56—Pseudomonas sp. IMBG163, довше зберігається необхідний титр бактерій, ніж у монокультурі Pseudomonas sp. IMBG163. A bacterial strain IMBG156 producing exopolysaccharide (EPS) was isolated from siliceous rock and identified as a Paenibacillus species by partial sequencing its 16S rDNA. Paenibacillus sp. IMBG156 was used in a novel technology for inoculant production based on co-cultivating this bacterium with any bacterium of choice. Paenibacillus sp. provides in situ the bacterial cells of the inoculant with EPS, a carrier, and most likely with a source of carbon and energy. The partner bacterium designates a type of inoculant (biopesticide or biofertiliser). The strain IMBG156 does not destroy the signaling system of Gram-negative partners, based on acylated homoserine lactones, stimulates plant growth, and is rather competitive in the plant rhizosphere and soil. A prototype of the inoculant based on dual-culture Paenibacillus sp. IMBG156 - Pseudomonas sp. IMBG163 exhibits a noticeably longer shelf life than monoculture of Pseudomonas sp. IMBG163.